INTEGRATIVE TECHNOLOGIES FOR INCREASING THE INTELLECTUAL ACTIVITY OF FUTURE ENGLISH LANGUAGE TEACHERS (Scientific journal of the Fergana State University, 2024)
The social order for a modern highly qualified specialist is determined in most cases by objective requirements for quality descriptions of the person and activity. It is the improvement of the quality of education that has a significant impact on the speed, quality and methods of implementing the social and economic policy of the state. There are certain difficulties in solving this task, which consist in the gap between the level of development of science and technology and the level of intellectual development of graduates of educational institutions, that is, a disconnection, and this problem is currently being actively discussed by a number of authors.This article describes the content and practical basis of integrative technologies for increasing the intellectual activity of future English language teachers.